Objectivity is an Elusive Ideal that Can Never be Achieved - Ajjan, Mazen (Richtmann Publishing, 2021)
The Paper investigates objectivity of Mass Media in the Middle East. The researcher chooses the most prominient news channel in that turbulent area of the world, namely Al-Jazeera Arabic news channel and examines its journey to claim its assumed objectivity. The paper gives analysis of objectivity in different cultureal contexts. It shows the ways Al-Jazeera established itself as an objective voice and how it presented itself as an alternative view to the dominant western perspective of global news. At the end the paper takes an intersting turn by bringing objectivity back to its